2010
DOI: 10.3126/ajms.v1i1.2607
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Iron Deficiency Anemia among Women of Reproductive Age in Hubei Province, China

Abstract: Objective: To assess the level of awareness about causes, prevention and treatment of iron deficiency anemia among women of reproductive age in Hubei province, a south eastern province of China.Method: Cross sectional study was conducted by using a self designed standardized pretested questionnaire in peripheral areas of Wuhan city, the capital of Hubei province from January 2009 to December 2009.Women aged 18-45 years without any previous history of medical or gynecological problems were recruited.Results: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
2
8
0
1
Order By: Relevance
“…In addition it is well known that birth spacing practice by mother prevents anaemia [2,10]. Similarly almost greater than half of mother reported that they strongly recommend iron supplementation, family planning for the prevention of IDA which is similar finding with the responses of pregnant mothers in this study [24,27].…”
Section: Open Access Freely Available Onlinesupporting
confidence: 85%
“…In addition it is well known that birth spacing practice by mother prevents anaemia [2,10]. Similarly almost greater than half of mother reported that they strongly recommend iron supplementation, family planning for the prevention of IDA which is similar finding with the responses of pregnant mothers in this study [24,27].…”
Section: Open Access Freely Available Onlinesupporting
confidence: 85%
“…According to the World Health Organization "anemia is a condition in which the number of RBCS or their oxygen-carrying capacity is insufficient to meet physiologic needs, which vary by age, sex, altitude, smoking, and pregnancy status [3]". It affects half a billion women of reproductive age worldwide that is 30.2% of non-pregnant and 41.8% of pregnant women aged 15-49 years [3]. The commonest type of anemia is IDA which is controlled by nutritional intake of Fe rich foods and taking IF supplementation [4], meanwhile women have less awareness about their health [5].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, anemia is serious public health problem with global prevalence of 48.8%, in Africa 40.7% for total population and 69% and 65.8% for global and African pregnant women respectively [3]. As Ethiopia is one of the low-income countries with poor health status and rapid population growth with 4.1 fertility rate [8], and has one of the highest rates of maternal mortality in Africa [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the participants in the study of Hussain T et al were all women (6). In a study conducted to determine the nutritional knowledge among adolescent girls, it was found that 30% girls knew about the sources of iron (7). On the other hand, 81(≈61 %) participants in this study thought that iron requirement of the body could be obtained mostly from the red meat ( Figure 2).…”
Section: Discussionmentioning
confidence: 66%